Determinan Prevalensi Stunting di Indonesia Tahun 2023 - Argyanti, Kadek; Novita, Resa Ferdhea; Pratama, Rizky Putra; Hayati, Zuhroini; Purwoto, Agus (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Stunting remains one of the major chronic nutritional problems faced by Indonesia. According to the 2023 Indonesia Health Survey, the national stunting prevalence stands at 21.5%, which is still above the threshold set by the World Health Organization (WHO) at 20%. This study aims to analyze the factors influencing the prevalence of stunting across provinces in Indonesia, specifically exclusive breastfeeding coverage, completeness of basic immunization, access to improved household sanitation, and the incidence of low-birth-weight (LBW) infants. The data used in this study are secondary aggregate data at the provincial level, obtained from the 2023 Indonesia Health Survey (IHS), Statistics Indonesia, and the Ministry of Health of the Republic of Indonesia. The analytical method employed is multiple linear regression with classical assumption testing. The results show that the incidence of LBW, completeness of basic immunization, and access to improved household sanitation significantly affect stunting prevalence. A higher incidence of LBW is associated with a higher stunting prevalence in a province. These findings are expected to serve as a basis for more effective and context-specific policy-making in accelerating efforts to reduce stunting in Indonesia.